The Mosque Waqf Model In The Concept Of Justice In The Distribution Of Wealth To The Community In Indonesia - Ayu Tridayana; Malahayatie; Taufiq (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2025)
This research examines mosque waqf management models in the context of wealth distribution justice in Indonesia, with the aim of understanding and mapping mosque waqf management practices on the islands of Sumatra, Java, and Kalimantan. The background of the problem raised is the inequality in the distribution of benefits of mosque waqf which is still consumptive and less productive, despite the enormous potential of waqf assets. The research method used is a literature review, with analysis of various relevant secondary data sources. The results show that mosque waqf management in Indonesia is still dominated by traditional approaches that prioritize physical development, while efforts to utilize assets productively are still limited. The conclusion of this study emphasizes the need for a more sustainable and productive mosque waqf management model to reduce economic inequality and improve community welfare